Effect of Hydrogen-Rich Water Soaking Combined with Polyethylene Nano-film Packaging on the Quality and Antioxidant Capacity of Agaricus bisporus during Postharvest Storage - SHEN Jiawei, YUN Jianmin, QING Chun, ZHANG Yajie, ZHAO Xueqi, LIU Jiaming, YAO Liang (Shipin Kexue)
To extend the shelf life of Agaricus bisporus, the optimal concentration and soaking time for hydrogen-rich water (HRW) treatment were selected through sensory evaluation as well as assessments of browning index, mass loss rate, and hardness. To investigate the effect of HRW combined with polyethylene (PE) nano (NA)-film packaging (HRW + NA) on the postharvest preservation of A. bisporus and to analyze the underlying mechanism, using HRW soaking combined with PE film packaging as the control, changes in the sensory quality, reactive oxygen species (ROS) metabolism, and antioxidant enzyme activity of HRW + NA treated mushrooms were dynamically monitored during low-temperature storage at (4 ± 1) ℃. The results showed that the selected HRW treatment conditions were soaking mushrooms in 50% HRW for 15 min. HRW + NA treated mushroom maintained better overall sensory quality with a fuller appearance, maintained better brightness value (L*), and showed a slower increase in ROS levels from days 9 to 15 of storage. Throughout the 15-day storage period, the activities of catalase (CAT), superoxide dismutase (SOD) and peroxidase (POD) remained higher in the HRW + NA treatment group. In summary, the combination of HRW soaking with NA-film packaging delayed the decline in the quality of A. bisporus during postharvest storage, extending the low-temperature shelf life by 5–6 days compared with conventional commercial PE film packaging.